Patient impressions of the impact of comorbidities on lung cancer screening benefits and harms: A qualitative analysis. (March 2023) - Kale, Minal S.; Diefenbach, Michael; Masse, Sybil; Kee, Dustin; Schnur, Julie
Abstract: Objective: To learn about the beliefs and preferences of lung cancer screening (LCS) among patients undergoing LCS decision making. Specifically, we investigated how their comorbidity influences their interest in screening. The goal was to inform shared-decision making discussions around the role of comorbidities and LCS. Methods: We recruited English-speaking LCS-eligible individuals with comorbidities from general medicine outpatient clinics at an academic medical center in New York City. The interviewers followed a semi-structured interview guide and all interviews were professionally transcribed. Study investigators independently conducted thematic analysis of de-identified transcripts; after coding, investigators discussed and agreed upon identified themes (Jacobs et al., 1999 [3]). This study was IRB-approved. Results: We achieved thematic saturation after 15 interviews. We identified the following themes: 1) Comorbidities were perceived as unrelated to LCS decision-making, 2) Lung cancer knowledge is valuable and worth any risks, 3) No matter what the guidelines or my providers say, the LCS decision is up to me. Conclusion/practice implications: Implications of these findings are that conversations where providers recommend against LCS may likely require time, patient education, and appreciation of the patient perspective.